Case report: Necrotizing leukomyelitis and meningitis in a Pomeranian - Santifort, Koen M.; Garosi, Laurent; Weerts, Erik A. W. S. (Frontiers in Veterinary Science, 2024)
A 2.5-year-old female entire Pomeranian dog was presented for acute paraparesis progressing within 2 days to paraplegia. General physical examination was unremarkable. Neurological examination showed paraplegia without nociception, a mass reflex upon testing perineal reflexes and withdrawal reflexes in the pelvic limbs and patellar hyperreflexia. Cutaneous trunci reflexes were absent caudal to the level of the 6th thoracic vertebra. Spinal hyperesthesia was present. Neuroanatomical localization was consistent with a T3-L3 myelopathy. Hematological and biochemical blood tests (including c-reactive protein (CRP)) were within reference ranges. MRI of the spinal cord from the level of the 1st thoracic vertebra to the sacrum revealed a patchy, ill-defined, moderate to marked T2W hyperintense, contrast enhancing intramedullary lesion extending from T1 to L4. Medical treatment based on a working diagnosis of meningomyelitis of unknown cause was initiated with corticosteroids and methadone based on pain scores. Prognosis was grave and after three days without return of nociception, the dog was euthanized according to the owners’ wishes. Post-mortem histopathological examination of the brain and spinal cord yielded a morphological diagnosis of severe, segmental, bilateral and fairly symmetrical, necrotizing lymphohistiocytic leukomyelitis, with a non-suppurative angiocentric leptomeningitis. Some minor, focal, lymphocytic perivascular cuffing was found in the medulla oblongata as well, but otherwise there were no signs of brain involvement. No infectious causes were identified with ancillary tests. This case report underlines the importance of including meningomyelitis in the differential diagnosis list of dogs presented for acute progressive neurological signs referable to a myelopathy.